A Phos‐tag SDS‐PAGE method that effectively uses phosphoproteomic data for profiling the phosphorylation dynamics of MEK1. Issue 13 (8th June 2016) - Kinoshita, Eiji; Kinoshita‐Kikuta, Emiko; Kubota, Yuji; Takekawa, Mutsuhiro; Koike, Tohru
Abstract : MEK1, an essential component of the mitogen‐activated protein kinase (MAPK) pathway, is phosphorylated during activation of the pathway; 12 phosphorylation sites have been identified in human MEK1 by MS‐based phosphoproteomic methods. By using Phos‐tag SDS‐PAGE, we found that multiple variants of MEK1 with different phosphorylation states are constitutively present in typical human cells. The Phos‐tag‐based strategy, which makes effective use of existing information on the location of phosphorylation sites, permits quantitative time‐course profiling of MEK1 phosphospecies in their respective phosphorylation states. By subsequent immunoblotting with an anti‐HaloTag antibody, we analyzed a HaloTag‐fused MEK1 protein and 12 potential phosphorylation‐site‐directed mutants of the protein transiently expressed in HEK 293 cells. This strategy revealed that MEK1 is constitutively and mainly phosphorylated at the Thr‐292, Ser‐298, Thr‐386, and Thr‐388 residues in vivo, and that combinations of phosphorylations at these four residues produce at least six phosphorylated variants of MEK1. Like the levels of phosphorylation of the Ser‐218 and Ser‐222 residues by RAF1, which have been well studied, the phosphorylation statuses of Thr‐292, Ser‐298, Thr‐386, and Thr‐388 residues vary widely during activation and deactivation of the MAPK pathway. Furthermore, we demonstrated inhibitor‐specific profiling of MEK1 phosphospecies by using three MEK inhibitors: TAK‐733, PD98059, and U0126.